Which entrepreneurs are financially constrained? - Ferreira, Miguel A. (2022)
We study what type of entrepreneurs are a ected by financial constraints by exploiting age-based discontinuities in the amount of funding available through a public program for unemployed workers. Our sample links administrative data on 2.1 million eligible workers to the firms they create, spanning a wide range of skills, sectors and outcomes. We find that access to funding increases the rate of entrepreneurship and that the e ect is stronger for entrepreneurs who incorporate their business, especially for those who were in the top decile of the wage distribution before unemployment. Among incorporated entrepreneurs, the effect is strongest in the information and communication sector, followed by manufacturing. In terms of ex-post outcomes, we find that the effect is more pronounced for businesses in the upper half of the size, growth and profitability distributions. Our findings suggest that financial constraints hamper growth-oriented entrepreneurship.